Sensory profiling and consumer acceptability of new dark cocoa bars containing Tuscan autochthonous food products. Issue 2 (28th November 2017) - Cantini, Claudio; Salusti, Patrizia; Romi, Marco; Francini, Alessandra; Sebastiani, Luca
Abstract: A new set of cocoa bars named Toscolata ® were developed containing top‐quality extra virgin olive oil, dried apples cultivars, and chestnut flour. The present work has been conducted to define the sensory profile of these products through tasting by trained experts and consumers to study the acceptability, preference, and quality perception. The four sensorial profiles of the bars differed in the level of persistence, bitterness, aromaticity, acidity, astringency, and tastiness. In particular, the sour attribute could be traced to the presence of dried apple. Bars containing apple and chestnut flour obtained higher acceptance ratings, compared to those with extra virgin olive oil. The bar with chestnut flour was preferred by consumers who considered it to be sweeter due to the presence of natural sugars, which lowered the bitter sensation of cocoa. These results showed that the selection of the preferred bar by consumers was mainly based on the level of bitterness and, in particular, elderly consumers expressed a strong preference for the sweetest product. As far as we know, this is the first study comparing the results of a panel of expert tasters with that of consumers in the tasting of dark chocolate. Abstract : A brand new set of cocoa bars were produced using top‐quality food products. The organoleptic profile of these bars was evaluated by a trained panel. Consumers' acceptability was finally studied to select the preferred products.